GIS analysis of landscape topography transformation of the open pit "Grivice" (Bosnia and Herzegovina) - Smajić, Sabahudin; Kadušić, Alma; Omerović, Almedin; Kovačević, Merima (Journal for Geography, 2020)
The authors analyze transformations of landscape topography of the open pit "Grivice" in Banovići basin (Northeastern Bosnia). This complex research is based on field screening and GIS analysis of Digital Elevation Models (DEMs) of researches terrain. Specifically, two DEMs of the Grivice area were prepared, a natural model based on a topographic map, scale 1:25000, issued in 1976 by the Military Geographical Institute (MGI) from Belgrade, while the Google satellite image from 2018 and the Digital Surface Model (DSM) were used for the anthropogenic model,issued in 2018 by the Japan Aerospace Exploration Agency (JAXA). Using methods and algorithms integrated in QGIS, raster and vector values of treated transformation parameters(hypsometry, slope and aspect, hydrographic network, etc.) were obtained, and their analytical-synthetic interpretation and geovisualization were also performed. Finally, ten thematic maps,which illustrate the anthropogenic transformation of the landscape topography of the researched area, were created.
Keywords: GIS analysis; landscape topography; transformation; DEM; geo-visualizations; open pit Grivice; Bosnia and Herzegovina